Identidades em trânsito : uma reflexão sobre a SGP - UFMT - Curvo, Leandro Dias (2018)
The world of contemporary work is permeated by complex interactions between people, organizational systems, and work environments. These interactions are marked by the phenomena of globalization: deterritorialization and decentering. These establish cultural interconnections making the identity arrangements hybrid, fragmented and transitory. In this way, identity configures itself as a consequence of the social process of an individual's attachment to a social and cultural system allowing it to be located and located within this system. Thus, this work arises from a study of the organizational climate carried out in the Secretariat of Personnel Management (SGP) - UFMT in 2015, which subsidizes us with data for a reading aimed at the discussion of identities. Therefore, the problem of this work is to understand how the notes located in the study of the organizational climate contribute to the construction of organizational and corporate identity? In this sense, the objective is to discuss the dynamics of the SGPUFMT server identification process based on an analysis of the data presented by the organizational climate study. The research is characterized as a qualitative-descriptive study, in which the instruments of data collection were the questionnaires applied to the servers of this administrative unit, systematic observation and participant of the work environment of these servers, as well as documentary research. The theoretical framework will be based on the approach of concepts related to globalization, cultural identity, corporate identity, organizational identity and all its necessary ramifications for the foundation of research. The main points were to understand the dynamics of belonging to the servers by the conceptual perspective of organizational identity (collective and shared perception of the values and characteristics of the organization) and how this reflects in the corporate identity (desired identity in order to obtain the most favorable image of the organization). It highlights the most relevant characteristics for the construction and understanding of the identities present in the organizational context such as: the organizational values and the way in which the employees feel represented by them, as well as the time of service in the institution, which crosses the professional profile of each server.